Dynamic Mode Decomposition with Control: A Case Study Of Covid-19 and Vaccination - Eroğlu, Simge Kacar; Yüksel, Gamze (Aydın KARAPINAR, 2023)
Epidemic diseases have posed great threats to human societies throughout history and have seriously affected public health. Epidemic diseases can spread rapidly and cause major deaths and economic losses. Therefore, the control and management of epidemic diseases requires new approaches developed with scientific and technological developments. The method of Dynamic Mode Decomposition with Control (DMDc) is a machine learning technique that predicts the state of systems, that affect the dynamic system from the outside and change the nature of the system. This technique is used to examine how the variables, factors, and effects in the data are related to each other and how they change over time. In this article, the DMDc method used the weekly cumulative number of Covid-19 cases per 100 thousand of Turkey's 81 provinces between February 8 and September 11, 2021, as the situation matrix, and the total number of vaccines per 100 thousand in the same date range as the control matrix and then calculated error values of the DMD and DMDc are compared with under the different error metrics. In this paper,the number of cases and vaccines in the Turkish Ministry of Health TURCOVID-19 open data set was used.

Epidemik hastalıklar tarih boyunca insan toplumlarına büyük tehditler oluşturmuş ve kamu sağlığını ciddi şekilde etkilemiştir. Epidemik hastalıklar hızla yayılabilir, büyük ölümlere ve ekonomik kayıplara yol açabilir. Bu nedenle, salgın hastalıkların kontrolü ve yönetimi, bilimsel ve teknolojik gelişmelerle birlikte geliştirilen yeni yaklaşımlar gerektirir. Dinamik Mod Ayrıştırmasında Kontrol (DMAk),dinamik sistemi dışarıdan etkileyen ve sistemin doğasını değiştiren sistemlerin durumunu tahmin eden bir makine öğrenmesi tekniğidir. Bu teknik, verilerdeki değişkenlerin, faktörlerin ve etkilerin birbirleriyle nasıl ilişkilendiklerini ve zamanla nasıl değiştiklerini incelemek için kullanılır. Bu çalışma da DMAk yönteminde 8 Şubat ile 11 Eylül 2021 tarihleri arasında Türkiye'nin 81 ilinin 100 bin kişideki haftalık kümülatif Covid-19 vaka sayısını durum matrisi, aynı tarih aralığında 100 bin kişideki toplam aşı sayısı kontrol matrisi olarak kullanıldı. Daha sonra Dinamik Mod Ayrıştırması (DMA) algoritması ve DMAk algoritmasının hesaplanan hata değerleri farklı hata metrikleri altında karşılaştırıldı. Bu çalışmada, Türkiye Sağlık Bakanlığı’nın Covid-19 vaka ve aşı sayısını içeren TURCOVID-19 açık veri kullanıldı.
Dinamik Mod Ayrıştırmasında Kontrol: Kovid-19 ve Aşılamaya İlişkin Bir Örnek Olay İncelemesi
Keywords: Software Engineering (Other); Yazılım Mühendisliği (Diğer)